Melatonin modulates neuroinflammatory response and microglial activation in mice exposed to dim blue light at night - Song, Chao; Suo, Zhaotaize; Wang, Zixu; Cao, Jing; Dong, Yulan; Chen, Yaoxing (Frontiers in Pharmacology, 2024)
Objectives Dim light at night contributes to neurodegenerative diseases by causing neuroinflammation. In the central nervous system, the activation of microglia is a significant contributor to neuroinflammation. Therefore, there is an urgent need to find an intervention to treat the neuroinflammatory response caused by dim light at night. Melatonin is a rhythmic hormone whose synthesis is suppressed during the day. In this study, we attempt to explore whether and how melatonin improves hippocampal neuroinflammation in mice exposed to dim blue light at night. Materials and Methods In vivo, a total of 36 male C57BL6/J mice that exposed to no light at night, dim blue light at night, and dim blue light at night with melatonin treatment. In vitro, the corticosterone-induced BV2 cells with or without melatonin treatment were used. Results Both in vivo and in vitro experiments showed melatonin treatment significantly reduced dim blue light -induced hippocampal microglial activation and the expression of inflammatory factors IL-1β and TNF-α. This improved effect of melatonin is related to its receptor MT2 rather than MT1. The MT2 blockers significantly increased mRNA levels of M1-type activation marker CD86 and inflammatory cytokines IL-1β and TNF-α in melatonin-treated BV2 cells. Binding of melatonin to its receptor MT2 downregulated the expression of inflammatory proteins P-P65 and NLRP3, consequently inhibited the CD80 expression and M1-type activation in microglia. Furthermore, consistent with the decrease in microglial activation and inflammatory response after melatonin treatment, we also observed a reduction in hippocampal neuron loss and damage to the HT22 cells. Conclusion Our findings suggested that melatonin may regulate microglial polarization through MT2/NF-kB-NLRP3 pathway and improves dim blue light -induced hippocampal neuroinflammation in mice.